The Role of Chemokine (C‐C Motif) Ligand 7 (CCL7) in Hepatocellular Carcinoma: Expression, Function, and Mechanisms - Yangkun Luo; Fei Wan; Zhao Zhang; Zujun Qin; Yongjun Ren (Cancer Medicine)
ABSTRACT Aim AHepatocellular carcinoma (HCC) is a malignant neoplasm characterized by a poor prognosis, with its incidence rising globally. Chemokine (C‐C motif) ligand 7 (CCL7), a chemokine protein, has been implicated in the progression of various cancers. Nonetheless, the specific role of CCL7 in HCC has yet to be elucidated. This study seeks to examine the expression and functional role of CCL7 in the context of HCC. Materials & Methods Western blot and immunohistochemistry were used to detect the expression of CCL7 in HCC tissues and cell lines. Cell Counting Kit 8 (CCK8) assay, clonogenic assay, and transwell assay were performed to examine the effects of CCL7 on SNU‐878 cells. Immunofluorescence was used to analyze the expression of proteins associated with epithelial interstitial transformation (EMT). Western blot was used to detect the activation of the PI3K/AKT pathway. In vivo tumorigenesis experiments were performed to assess the role of CCL7 in HCC tumorigenesis. Results The results showed that the expression of CCL7 was up‐regulated in HCC tissues, and exogenous CCL7 promoted the proliferation, migration, invasion, and EMT of SNU‐878 cells and VEGF secretion by SNU‐878 cells. Furthermore, CCL7 stimulated the activation of the PI3K/AKT pathway. Further analysis revealed that CCL7 targeted CCR1 and CCR2 to enhance the growth, and metastasis of SNU‐878 cells and VEGF secretion by SNU‐878 cells. CCR1/CCR2 silencing prevented CCL7 from activating the PI3K/AKT signaling pathway in SNU‐878 cells. Moreover, CCL7 facilitated HCC tumorigenesis and VEGF expression in vivo. Conclusion Our findings indicate that CCL7 plays a promoting role in HCC growth and tumorigenesis, potentially via targeting CCR1 and CCR2 and activating the PI3K/AKT pathway.